186 NRF2 regulation of the interferon signature in lupus macrophages. (April 2019) - Han, Shuhong; Zhuang, Haoyang; Lee, Pui; Li, Mingjia; Nigrovic, Peter; Reeves, Westley H
Abstract : Background: Peripheral blood cells from two-thirds of adult lupus patients exhibit a gene expression program (interferon signature) attributed to the over-production of interferon (IFN) and other type I IFNs (IFN-I). IFN-I may be involved in the pathogenesis of lupus. Although plasmacytoid dendritic cells produce large amounts of IFN-I, our studies in an experimental lupus model suggest that macrophages and/or monocytes may play an important role in generating the interferon signature. This study sought to define how macrophages influence the interferon signature. Methods: Proinflammatory and anti-inflammatory (pro-resolving) macrophages were isolated from mice with pristane-induced lupus and were analyzed by RNA-sequencing (RNA-Seq) and quantitative PCR (qPCR). Protein expression in macrophage subsets was evaluated by flow cytometry. The role of nuclear factor erythroid 2 like 2 (Nrf2) activators was examined in vivo Results: Transcriptional profiling (RNA-Seq) of CD11b+Ly6G- peritoneal macrophages from mice with experimental lupus unexpectedly indicated a strong interferon signature in proinflammatory (Ly6ChiCD138-), but not anti-inflammatory (Ly6C-CD138+), macrophages exposed to the same IFN-I concentrations. Along with higher IFN-I regulated gene expression, proinflammatory macrophages expressed lower levels of genes regulated by nuclear factor erythroid 2 like 2 (Nrf2) than anti-inflammatory macrophages. Transcript levels of IFN receptor 1 chain (Ifnar1), IFNAR surface staining, and mitochondrial superoxide all were higher in proinflammatory macrophages. Administration of the Nrf2 activator CDDO-Im to lupus mice decreased IFNAR expression, blocked IFN-driven Stat1 phosphorylation, and reduced IFN-regulated gene expression. Thus, the interferon signature in murine lupus critically depends on Nrf2-regulated changes in IFNAR expression in macrophages. Human peripheral blood mononuclear cells exhibited a similar pattern: high IFNAR expression in classical monocytes and lower levels in non-classical monocytes. The data suggest that anti-inflammatory macrophages/monocytes are insensitive to IFN signaling, potentially serving a role in the resolution of inflammation. Conclusions: These studies reveal that the relative abundance of different monocyte/macrophage subsets (proinflammatory vs. anti-inflammatory/pro-resolving) helps determine the magnitude of the interferon signature. In addition to reflecting IFN-I production, the interferon signature critically depends on the Nrf2-regulated responsiveness of macrophages to signaling through the IFNAR. These studies provide a new perspective on the interferon signature that may have implications for understanding the pathogenesis of lupus. In addition, these studies suggest that Nrf2 activators could have a role in the therapy of lupus. Funding Source(s): NIH